Detrimental for Some? Heterogeneous Effects of Maternal Incarceration on Child Wellbeing. Issue 1 (24th January 2015) - Turney, Kristin; Wildeman, Christopher
<x xml:space="preserve">Abstract</x> Research Summary We use data from the Fragile Families and Child Wellbeing Study (N = 3, 197) to consider the heterogeneous effects of maternal incarceration on 9‐year‐old children. We find that maternal incarceration has no average effects on child wellbeing (measured by caregiver‐reported internalizing problem behaviors, caregiver‐reported externalizing problem behaviors, Peabody Picture Vocabulary Test‐Third Edition scores, and child‐reported early juvenile delinquency) but that the effects vary by mothers' propensities for experiencing incarceration. Maternal incarceration is deleterious for children of mothers least likely to experience incarceration but mostly inconsequential for children of mothers more likely to experience incarceration. Policy Implications It is important that public policies take into account the fact that not all children experience similar effects of maternal incarceration. For children of mothers who are unlikely to experience incarceration, the negative consequences of maternal incarceration could be driven by at least three factors, all of which may operate simultaneously and all of which potentially call for different policy interventions: (a) jail incarceration as opposed to prison incarceration, (b) incarceration for a crime that did minimal—or no—harm to their children, and (c) inadequate family supports for coping with maternal incarceration. We discuss these policy implications.